Mekanisme Perhitungan dan Pelaporan Pajak Penghasilan Pasal 21 Karyawan Tetap dengan Menerima Insentif Pajak: Income Tax Calculation and Reporting Mechanism Article 21 Permanent Employees Receiving Tax Incentives - Zannuba Arifa, Silvia (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2023)
The purpose of this study is to find out the mechanism for calculating Article 21 Income Tax by receiving Tax Incentives from the Government for deduction and reporting of Employees' Fixed Annual Income Tax. This type of research is descriptive research with a case study research approach on the status of research subjects with respect to certain phases or typical of the whole personality. Data obtained from documentation, namely data on permanent employee earnings, calculation of PPh Article 21, and form 1721 A1. The unit of analysis in this study is the tax consultant client employees that I studied. In carrying out the calculation and reporting of Article 21 Income Tax, it is carried out as well as possible so as not to get sanctions if there is an error or delay in calculating or reporting the client's Article 21 Income Tax. Calculations made in accordance with the tax provisions in force at that time.